Hunger Solution: One-Dimensional and Multi-Dimensional Food Security Programs - Saada Reuveni (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Addressing hunger requires many different programs to tackle this issue. These programs need to be organized in an effective way, and so far, no evidence exists of attempts made to categorize hunger solution programs. This study takes the first step in suggesting a new approach to hunger program categorization. The two categories suggested are one-dimensional hunger programs and multi-dimensional hunger programs. The first category emphasizes a solution focused on one channel of activity to address the hunger problem. The second category emphasizes that hunger is a complex, multi-dimensional problem that requires a multi-pronged solution, working simultaneously through several channels to address hunger. This study tests six food security programs, discusses each profile’s working plans, and determines which category each program applies to. Categorization makes the study of hunger programs much easier and helps to identify similarity between proposes solutions. It has a practical side too. For example, it could serve as a basis for developing other new ideas for this issue or help to compare and determine effective programs or solutions. The two categories offered in this study for food security programs could also be easily applied to other hunger programs.